In vitro activity of cefiderocol against European Pseudomonas aeruginosa and Acinetobacter spp., including isolates resistant to meropenem and recent β-lactam/β-lactamase inhibitor combinations - Anne Santerre Henriksen; Katy Jeannot; Antonio Oliver; John D. Perry; Mathias W. Pletz; Stefania Stefani; Ian Morrissey; Christopher Longshaw (Microbiology Spectrum, 2024)
ABSTRACTCarbapenem-resistant Pseudomonas aeruginosa and Acinetobacter spp. represent major threats and have few approved therapeutic options. Non-‍fermenting Gram-negative isolates were collected from hospitalized inpatients from 49 sites in 6 European countries between 01 January 2020 and 31 December 2020 and underwent susceptibility testing against cefiderocol and β-lactam/β-lactamase inhibitor combinations. Meropenem-resistant (MIC >8 mg/L), cefiderocol-susceptible isolates were analyzed by PCR, and cefiderocol-resistant isolates were analyzed by whole-genome sequencing to identify resistance mechanisms. Overall, 1,451 (950 P. aeruginosa; 501 Acinetobacter spp.) isolates were collected, commonly from the respiratory tract (42.0% and 39.3%, respectively). Cefiderocol susceptibility was higher than ‍β‍-‍l‍a‍c‍t‍a‍m‍/‍β‍-‍l‍a‍c‍t‍a‍mase‍ inhibitor combinations against P. aeruginosa (98.9% vs 83.3%–91.4%), and P. ‍aeruginosa resistant to meropenem (n = 139; 97.8% vs 12.2%–59.7%), β-lactam/β-lactamase inhibitor combinations (93.6%–98.1% vs 10.7%–71.8%), and both meropenem and ceftazidime-avibactam (96.7% vs 5.0%–‍‍45.0%) or ‍ceftolozane-tazobactam (98.4% vs 8.1%–54.8%), respectively. Cefiderocol and sulbactam-durlobactam susceptibilities were high against Acinetobacter spp. (92.4% and 97.0%) and meropenem-resistant Acineto‍bacter ‍spp. (n = 227; 85.0% and 93.8%) but lower against sulbactam-durlobactam- (n ‍= 15; 13.3%) and cefiderocol- (n = 38; 65.8%) resistant isolates, respectively. Among meropenem-resistant P. aeruginosa and Acinetobacter spp., the most common β-‍‍lactamase genes were metallo-β-lactamases [30/139; blaVIM-2 (15/139)] and oxacillinases [215/227; blaOXA-23 (194/227)], respectively. Acquired β-lactamase genes were identified in 1/10 and 32/38 of cefiderocol-resistant P. aeruginosa and Acinetobacter spp., and pirA-like or piuA mutations in 10/10 and 37/38, respectively. Conclusion: cefiderocol susceptibility was high against P. aeruginosa and Acinetobacter spp., including meropenem-resistant isolates and those resistant to recent β-lactam/β-lactamase inhibitor combinations common in first-line treatment of European non-fermenters.IMPORTANCEThis was the first study in which the in vitro activity of cefiderocol and non-licensed β-lactam/β-lactamase inhibitor combinations were directly compared against Pseudomonas aeruginosa and Acinetobacter spp., including meropenem- and β-lactam/β-lactamase inhibitor combination-resistant isolates. A notably large number of European isolates were collected. Meropenem resistance was defined according to the MIC breakpoint for high-dose meropenem, ensuring that data reflect antibiotic activity against isolates that would remain meropenem resistant in the clinic. Cefiderocol susceptibility was high against non-fermenters, and there was no apparent cross resistance between cefiderocol and β-lactam/β-lactamase inhibitor combinations, with the exception of sulbactam-durlobactam. These results provide insights into therapeutic options for infections due to resistant P. aeruginosa and Acinetobacter spp. and indicate how early susceptibility testing of cefiderocol in parallel with β-lactam/β-lactamase inhibitor combinations will allow clinicians to choose the effective treatment(s) from all available options. This is particularly important as current treatment options against non-fermenters are limited.